Let the number consist of the digits x and y, or it is represented by xy. It is given that adding 27 to the number causes the digits to get interchanged:(xy + 27) = yx

We can write this as (10*x + y) + 27 = 10y + x

=>...

## See

This Answer NowStart your **48-hour free trial** to unlock this answer and thousands more. Enjoy eNotes ad-free and cancel anytime.

Already a member? Log in here.

Let the number consist of the digits x and y, or it is represented by xy. It is given that adding 27 to the number causes the digits to get interchanged:(xy + 27) = yx

We can write this as (10*x + y) + 27 = 10y + x

=> 10x + y + 27 = 10y + x

=> 27 = 9y – 9x

=> 3 = y – x

=> y = 3 + x

To satisfy the relation y = 3 + x, x can take the values 1 , 2, 3 , 4, 5 and 6. y would be equal to 4 , 5, 6, 7 , 8 and 9

**The required two digit number can be 14 , 25, 36, 47, 58 and 69**